2014
DOI: 10.2174/1568009614666140331231658
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Regulates TXNIP/TRX/ROS Axis via p38 MAPK and ERK Pathways in Pancreatic Cancer

Abstract: Approximately 85% of pancreatic cancer patients suffer from glucose intolerance or even diabetes because high glucose levels can contribute to oxidative stress which promotes tumor development. As one of the reactive oxygen species (ROS)-regulating factors, thioredoxin-interacting protein (TXNIP), is involved in the maintenance of thioredoxin (TRX)-mediated redox regulation. In this study, we demonstrated that high glucose levels increased the expression of TXNIP in time- and concentration-dependent manners an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Deprivation of glucose induced supra-physiological levels of phospho-tyrosine signaling and a modest increase in phosphorylation of AMPK, AKT, and p42/44 in breast, kidney, lung, colon, prostate and ovarian cancer cells [21, 3436]. On the other hand, it has recently been reported that high glucose stimulated phosphorylation of AKT, reduced AMPK phosphorylation and activated MAPK pathways in cancer cells [3740]. These studies suggest these signaling pathways have switch-like properties that produce differential kinetics under different metabolic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Deprivation of glucose induced supra-physiological levels of phospho-tyrosine signaling and a modest increase in phosphorylation of AMPK, AKT, and p42/44 in breast, kidney, lung, colon, prostate and ovarian cancer cells [21, 3436]. On the other hand, it has recently been reported that high glucose stimulated phosphorylation of AKT, reduced AMPK phosphorylation and activated MAPK pathways in cancer cells [3740]. These studies suggest these signaling pathways have switch-like properties that produce differential kinetics under different metabolic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tyagi et al (8) indicated that P-21 activated kinase 4 promotes the proliferation and survival of pancreatic cancer cells via the ERK pathway. In addition, Li et al (9) reported that hyperglycemia regulates the thioredoxin-interacting protein/ thioredoxin/reactive oxygen species axis of pancreatic cancer via the p38 MAPK and ERK pathways. Zheng et al (10) reported that gemcitabine inhibited tumour growth and promoted apoptosis of pancreatic cancer via upregulation of pERK1/2 levels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that ROS induced TXNIP may impair the ability of cells to remove intracellular ROS (23,50,51), while increased intracellular ROS may contribute to the metastatic process of HBV-associated HCC (23,24,52). Whether TXNIP is involved in HBx-induced metastasis of HBV-associated HCC is worthy of further study.…”
Section: Discussionmentioning
confidence: 96%
“…HBx is involved in metastasis of HBV-associated HCC by various means, including upregulating intracellular ROS levels (23,24). Acting as a key mediatory factor of intracellular ROS level, TXNIP is involved in the progression of numerous types of tumor (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation